A generalized Nusselt number correlation for nanofluids, and look-up diagrams to select a heat transfer fluid for medium temperature solar thermal applications. (25th May 2021) - Upadhyay, Satish; Chandra, Laltu; Sarkar, Jahar
Highlights: A non-dimensional figure of merit is proposed for evaluating heat transfer fluids. A generalized form of Nu correlation, for nanofluids, is proposed using a novel separation approach. Figure of merit based look-up diagrams are developed to enable the selection of heat transfer fluids. Vegetable oil or vegetable oil based nanofluids are beneficial for medium temperature solar thermal. Abstract: There are many solar thermal applications in the medium temperature range, 373–573 K. These systems rely heavily on heat transfer fluids. Proper strategy and heat transfer correlation are required for selecting heat transfer fluids. Hence, a consistent, non-dimensional figure of merit is proposed for heat transfer fluids, like synthetic oils, widely-available vegetable oils, and molten salts. To extend this analysis for nanofluids, a correlation for Nusselt number ( Nu ) is deduced, using the experimental data, for nanoparticles with distinct thermo-physical properties, shapes and sizes. A novel separation approach is proposed to filter the effect of nanoparticles on Nu correlation for nanofluids. This leads to a generalized form of Nu correlation for nanofluids, which allows the use of a well-accepted Nu correlation for a wide-range of base-fluid. The generalized form of Nu correlation, for nanofluids, predicts the experiment-based Nu for CuO-water, TiO2 -water, Cu-water, Carbon nanotube-water, mostly within ±20%, with an exception of Graphene nanoplatelet. One way to adopt this approach, for hybrid-nanofluids, is discussed. The figure of merit-based qualitative and quantitative look-up diagrams are developed to enable the selection of heat transfer fluids. A comparative assessment shows that the figure of merit, for CuO-Canola/TherminolVP1 nano-oil or CuO-Al2 O3 -Canola/TherminolVP1 hybrid nano-oil increases by about 10-30%, in comparison to Canola or TherminolVP1 oil. Therefore, the use of Canola oil and Canola oil-based nano-oil or hybrid-nano-oil will be beneficial for solar thermal systems in the medium temperature range. Moreover, the use of TherminolVP1 based nano-oil or hybrid nano-oil will be beneficial for concentrated solar thermal power generation systems. A preliminary cost-benefit analysis lends additional support to these findings.